Navigating the peer-to-peer workflow in non-formal education through an innovative e-learning platform: a case study of the KIDS4ALLL educational project in Hungary and Italy - Schroot, Tanja; Lőrincz, Borbála; Bernát, Anikó (Frontiers in Human Dynamics, 2024)
The digital revolution is affecting all aspects of life, radically transforming everyday tasks and routines. The ability to cope with new challenges in life, including new forms of learning are key skills in the 21st-century, however, education systems often struggle with tackling digital inequalities. A digital learning platform developed by the KIDS4ALLL educational project, implemented in face-to-face student interactions, aims to mitigate the divide and the resulting social disadvantages among children with and without migration/ethnic minority background. Analysing data collected during the pilot phase of the project in two of the participating countries, Italy and Hungary, this paper examines how students and teaching staff adapt to a newly introduced digital learning tool based on peer-to-peer workflows. Firstly, it examines the role of educators' interpersonal competences in navigating the innovative learning activities and delves into how they use them and how they manage resources. Secondly, the study explores what attitudes and behaviours are observed among students engaged in the proposed peer-led activities, in particular in terms of their ability to cope with uncertainty and complexity. The analytical framework of the paper is based on two cultural dimensions offered by Hofstede (2001), the index of uncertainty avoidance (UAI) and power distance (PDI), and it utilizes the personal, social and learning-to-learn competence of the 8 LLL Key Competences as defined by the European Commission to conceptualize the skills of educators and students. Interpreting data from Italy and Hungary in their respective social and educational contexts, the study finds that the most important features that proved to be effective and useful during the pilot phase were the democratic power-relations between students and educators, the peer-to-peer scheme and its further development to the peer-for-peer approach. The child-friendly and real-life-related new curriculum and its appealing digital learning platform, embedded into a flexible, playful and child-centred pedagogical approach, were also successful. These are all complementing the traditional, formal school environment and pedagogy which, despite all developments in formal education in the past decades, can be characterized as teacher-centred and frontal.